2021
DOI: 10.3390/rs13245140
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Salinity Content in Different Saline-Alkali Zones Based on Machine Learning Model Using FOD Pretreatment Method

Abstract: Soil salinization is a global ecological and environmental problem in arid and semi-arid areas that can be ameliorated via soil management, visible-near infrared-shortwave infrared (VNIR-SWIR) spectroscopy can be adapted to rapidly monitor soil salinity content. This study explored the potential of Grünwald–Letnikov fractional-order derivative (FOD), feature band selection methods, nonlinear partial least squares regression (PLSR), and four machine learning models to estimate the soil salinity content using VN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Chen et al 47 . and Fu et al 48 . similarly obtained opposite comparative results when using RF and ELM for SSC prediction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chen et al 47 . and Fu et al 48 . similarly obtained opposite comparative results when using RF and ELM for SSC prediction.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the results of Qi et al 45 showed that RF outperformed SVM in predicting SSC, whereas Wang et al 46 showed that SVM outperformed RF. Chen et al 47 and Fu et al 48 similarly obtained opposite comparative results when using RF and ELM for SSC prediction. Based on this, both the size of the dataset and the choice of model need to be considered in future studies to achieve the best inversion results.…”
Section: Performance Of the Ssc Prediction Modelsmentioning
confidence: 98%
“…Modeling strategy I used only the single-band feature variables screened by CARS to participate in the modeling, and the results showed that the 1.9 order was the optimal differential order which was the same as the optimal differential order for region I in the study of salinity content estimation in different saline zones by ( Fu C. et al., 2021 ). The characteristic bands were scattered in the visible (408-777 nm), but mainly concentrated in the near-infrared (NIR) shortwave (800-1000 nm), which indicated that the NIR bands performed better in the characterization of soil salinity using vegetation spectra, which was also confirmed in the results of ( Tian et al., 2021 ) and ( Nguyen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A correlation coefficient was used to measure the relationship between the variables and their strength [69,70]. This plays a very important role in dimensionality reduction of sample data and missing value estimations [71].…”
Section: Multivariate Statistical Analysis (Msa)mentioning
confidence: 99%